Khan Academy como herramienta en el aprendizaje de las matemáticas y la programación (2021)
The research identified the perception of the relationship between mathematics and computer science, and how the Khan Academy helps study in these areas. The mathematical and computing relationship, fundamental in the development of new technologies, must be taught with a constructivist and connectivist approach, and supported by ICT, seeking for the student to develop from an early age their abilities and interest in STEM careers. It is concluded that the use of Khan Academy was very positive, showing that for 83% of the students the tool managed to solve many of their questions. Likewise, for 67%, the topics covered in the selected courses allowed them to learn or reinforce their knowledge, and for 82%, the platform obtained a score between 4 and 5 points of acceptance in the use of the platform